Propaganda, printing freedom and circulation of ideas: the English influence in the Mediterranean World (1794-1818) - de Salvo, Patrizia (Cuadernos de Historia Moderna, 2013)
This contribution examines Britain’s influence in the formation of a controlled information in the Mediterranean area from 1790 to 1818. The wide circulation of ideas that characterized this period, the gradual spread of culture, the new ‘spaces of sociability’ and, finally, the increasingly widespread use of newspapers and gazettes, allowed to a widespread audience to become the interpreters of the postulates of modern constitutionalism. The historical background is the Anti-Jacobin War and the confrontation with Napoleon in the Mediterranean, from the founding of the Anglo-Corsican Kingdom in 1793 to the establishment of the United States of the Ionian Isles in 1815. This paper demonstrates how the idea of ‘psychological warfare’ appears directly linked to the concept of public opinion as a political subject.
Keywords: euro-mediterranean Constitutionalism; newspapers; propaganda; public opinion; Great Britain